Pre-Hispanic dogs of the Semi-arid North of Chile: Chronology, morphology and mortuary context of the El Olivar site - González Venanzi, Lucio; Prevosti, Francisco Juan; González, Paola; Cantarutti, Gabriel; López Mendoza, Patricio Gonzalo; Prates, Luciano Raúl (Journal of Archaeological Science: Reports)
The article presents an analysis of four canid skeletons recovered at the El Olivar archaeological site (Semi-arid North of Chile). The aims of the study were to determine their taxonomy and chronology, characterise their morphotypes and investigate their social status and possible functions. Osteological and dental features allowed us to identify them as dogs (Canis lupus familiaris). Three radiocarbon dates gave pre-Inca ages (801 ± 19, 932 ± 21 and 789 ± 20 years 14C BP), associated with contexts of the Late Intermediate or Diaguita Period. These new records expand the pre-Hispanic distribution of the species, previously limited to the Arid North and the extreme south of the country. They were medium or medium-small in size, their approximate body weight and height at the withers were 13–14 kg and 48 cm respectively, and they were probably mesocephalic. At least three of the dogs were buried individually in a sector devoted to human burials, one with funerary offerings similar to those found with humans. These characteristics suggest that the dogs buried here were companion animals, with clear social recognition. Evidence was also recorded suggesting that one might have been killed intentionally. Fil: González Venanzi, Lucio. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Arqueología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Prevosti, Francisco Juan. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Rioja; Argentina Fil: González, Paola. No especifíca; Fil: Cantarutti, Gabriel. No especifíca; Fil: López Mendoza, Patricio Gonzalo. No especifíca; Fil: Prates, Luciano Raúl. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Arqueología; Argentina